Investigating Senior High School Students’ Conceptual Understanding of Heat and Temperature: A Qualitative Analysis in Physics Education - Utama, Rodika; Toifur, Moh.; Ishafit, Ishafit; Okimustava, Okimustava (Jurnal Pendidikan Fisika FKIP UM Metro, 2025)
The distinction between heat and temperature is fundamental in physics learning, yet it remains a persistent source of student misconceptions. Many learners interpret heat as a tangible substance stored within an object or assume that temperature is equivalent to the amount of heat possessed. Such misunderstandings hinder the development of deeper concepts in thermodynamics and energy transfer. This study aims to investigate senior high school students’ conceptual understanding of heat and temperature through a qualitative lens. The research involved 30 Grade XI students from a public high school in Indonesia. Data were collected using a conceptual diagnostic test followed by semi-structured interviews that probed students’ reasoning about everyday thermal phenomena. Thematic analysis was applied to categorize misconceptions and identify underlying reasoning models. Findings revealed four dominant patterns: (1) the substance model of heat, where students described heat as a material that flows from hot to cold bodies; (2) the equation model of temperature, in which temperature was mistakenly treated as the total amount of heat; (3) the cold transfer misconception, where students believed coldness itself moves from one body to another; and (4) the size–temperature confusion, where larger objects were assumed to always have higher temperature. These conceptions align with reports in international literature, indicating the universal nature of such difficulties. The study underscores the value of qualitative exploration for uncovering the reasoning behind misconceptions, not merely their frequency. Implications for teaching include the use of particle-level representations, predict–observe–explain activities, and simple calorimetry experiments to help students reconstruct scientifically accurate models of heat and temperature.